STATUS AND LEGAL PROTECTION OF THE AMUNGME AND KAMORO INDIGENOUS COMMUNITIES IN CONTRACT RENEGOTIATION OF PT.FREEPORT INDONESIA - Kanisius Jehabut; Eriyantouw Wahid; Gunawan Djajaputra (RADJA PUBLIKA, 2023)
This research discusses the existence of indigenous peoples of the Amungme tribe and Kamoro tribe in the application of Law No. 4 of 2009 concerning Mineral and Coal Mining ( Minerba Law), renegotiation of contracts of work of PT. Freeport Indonesia is in connection with the Divestment of Shares , the legal position and involvement of the indigenous peoples of the Amungme and Kamoro Tribes and the economic rights of indigenous peoples affected by pt. Freepoint Indonesia. As is known that PT Freeport Indonesia is a mining company company that has a Contract of Work (KK) in the Grasberg and Ertsberg Mountains mining area which began in 1967 and will only end in 2021. Since implementation of the Minerba Law, PT. Freeport is required to dive shares to the Indonesian Government . in the process of divestment of shares , the the government has not been involved indigenous peoples who have customary rights in the mining area so that there are several problems such as conflicts in the mining area caused by the absences of arrangements regarding minerals and coal business in accordance with Pancasila and the 1945 Constitution , because the Minerba Law is only able to reach legal actions after the issuance of the Minerba Law and related matters related to KK that existed before the Minerba Law. in the other hand , the existence of KK PT. Freeport Indonesia is considered incompatible with Pancasila, namely the Fifth Precept